RNA-Binding Motif 4 (RBM4) Suppresses Tumor Growth and Metastasis in Human Gastric Cancer - Yong, Hongmei (Med Sci Monit, 2019)
BACKGROUND: Dysregulation of the splicing activator, RNA-binding motif 4 (RBM4), has recently been reported to be involved in the progression of several cancers. However, the mechanisms that underpin the activity of RBM4 in gastric cancer (GC) remain unknown. The purpose of our study was to explore how RBM4 affects the biological behavior of GC through in vivo and in vitro experiments. MATERIAL/METHODS: Western blot and flow cytometry analyses were used to investigate the RBM4 protein levels in normal gastric epithelial cells and 5 types of GC cells. Cell Counting Kit-8 assay, flow cytometry analysis, wound-healing, and migration and invasion assays were evaluated in vitro in BGC823 and MGC803 GC cells. A xenograft tumor model was used to assess whether RBM4 inhibits GC growth in vivo. Mitogen-activated protein kinase (MAPK) protein levels were determined using western blot analyses. RESULTS: Our study revealed that RBM4 protein was downregulated in GC cells. Re-expression of RBM4 inhibited the proliferation, migration, and invasion of GC cells, while promoting apoptosis. Thus, the overexpression of RBM4 can inhibit tumor growth in GC mouse models. We also report that RBM4 was involved in the activation of MAPK-dependent signaling pathways in human GC. CONCLUSIONS: It is hoped that these findings will improve our understanding of GC pathogenesis while also helping us to explore the feasibility of RBM4-targeted therapy for GC treatment.